2006
DOI: 10.1111/j.1365-2486.2006.01109.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil‐atmospheric exchange of CO2, CH4, and N2O in three subtropical forest ecosystems in southern China

Abstract: The magnitude, temporal, and spatial patterns of soil-atmospheric greenhouse gas (hereafter referred to as GHG) exchanges in forests near the Tropic of Cancer are still highly uncertain. To contribute towards an improvement of actual estimates, soil-atmospheric CO 2 , CH 4 , and N 2 O fluxes were measured in three successional subtropical forests at the Dinghushan Nature Reserve (hereafter referred to as DNR) in southern China. Soils in DNR forests behaved as N 2 O sources and CH 4 sinks. Annual mean CO 2 , N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

52
208
6
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(278 citation statements)
references
References 67 publications
52
208
6
2
Order By: Relevance
“…However, this was in contrast with the finding from a similar study by Tang et al (2006), who only reported a reasonable correlation between soil moisture and N 2 O emissions. In our study, statistical positive relationship between N 2 O emissions and soil moisture were detected in orchard plots, which were in line with the former studies (Tang et al 2006;Liu et al 2008). Nevertheless, the stimulation of soil moisture on N 2 O fluxes may be significant at dry soils and wet soils (Lin et al 2012).…”
Section: Dependence Of Soil Ch 4 and N 2 O On Soil Propertiescontrasting
confidence: 99%
See 1 more Smart Citation
“…However, this was in contrast with the finding from a similar study by Tang et al (2006), who only reported a reasonable correlation between soil moisture and N 2 O emissions. In our study, statistical positive relationship between N 2 O emissions and soil moisture were detected in orchard plots, which were in line with the former studies (Tang et al 2006;Liu et al 2008). Nevertheless, the stimulation of soil moisture on N 2 O fluxes may be significant at dry soils and wet soils (Lin et al 2012).…”
Section: Dependence Of Soil Ch 4 and N 2 O On Soil Propertiescontrasting
confidence: 99%
“…Generally, temperature regulated the N 2 O emissions through its influence on nitrifying and denitrifying activity (Burger et al 2005). However, this was in contrast with the finding from a similar study by Tang et al (2006), who only reported a reasonable correlation between soil moisture and N 2 O emissions. In our study, statistical positive relationship between N 2 O emissions and soil moisture were detected in orchard plots, which were in line with the former studies (Tang et al 2006;Liu et al 2008).…”
Section: Dependence Of Soil Ch 4 and N 2 O On Soil Propertiesmentioning
confidence: 66%
“…Correlation analysis in the current study showed that there did not exist a significant relationship between air or soil temperatures and N 2 O emissions in P. australis community, but the significant relationship between N 2 O emissions and temperature was found in other three positions. Tang et al (2006) suggested that soil temperature did not have a strong effect on N 2 O emissions, which was consistent with results reported in tropical, agricultural soils (Crill et al, 2000;Kiese and Butterbach-Bahl, 2002). On the other hand, some studies showed that N 2 O fluxes were strongly correlated with soil temperature.…”
Section: Discussionsupporting
confidence: 79%
“…5), and more than 60.4% and 68.2% of the seasonal variability covering all four periods in 2006 and 2007, respectively. Such a strong temperature dependence of SCE has also been reported in other studies of subtropical forest ecosystems (Tang et al 2006;Saiz et al 2006;Sheng et al 2010), temperate semiarid grassland (Jin et al 2009b) and agro ecosystems (Han et al 2007;Meijide et al 2010). In these ecosystems, the SCE exhibited a distinct seasonal variation that paralleled the seasonality observed in soil temperature (Saiz et al 2006); the peak values could be explained by temperature.…”
Section: Discussionsupporting
confidence: 56%